The politics of production and distribution of resources in the small-scale Fisheries sector Olotayan Isla, Roxas City, Capiz. - Roxas, Frances Therese (2012.)
The study aims to describe the socio-economic relationships aring in the production and distribution sector of the small-scale fisheries industry. The research e3mploys three aspects to describe such relationships: (1) power, (2) depende3nce and (3) perception of fairness. The study was conducted in different areas in Roxas City where fish production and marketing activities take place namely Brgy. Olotayan, Brgay. Banica landing area and teodoro Arcenas Trade Center. Lastly, the research aimes to describe the government interventions that the local government of Roxas City extended in the form of markey regulations, credit assistance and technical assistance. The research found out that in the production sector, the crewmen are dependent to boat owners in terms of materials for fishing and credit access. On the other hand, the boat owners are also dependent on the broker in terms of credit access and materials for production (i.e. crude oil/gasoline). The broker?s interest is the security of supply and is less mindful of the repayment of debts. The brokers and retailers are less dependent on each other due to the availability of the services that other sources give. The broker-wholesaler/biahero dyad exhibits an interdepentdent relationship. Credit assistance for fishermen?s cooperatives were discontinued due to nonrepayment of debts. The current projects of the government were focused on (1) ecotourism and (2) aternative livelihood which i8mplies non-provision of technology for fishing livelihood per se. Economic transaction related to fishing industry in Banica landing area are not regutaled by the City government though economic transactions in TATC (trade center) are regulated by Office of the City Mayor.
Research Project (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2012.
Keywords: Small-scale Fisheries Sector -- Roxas City -- Research